Experimental data on the relationship between dyes sensitizers and wavelength during the photocatalytic degradation of diclofenac - Diaz Angulo, J.; Porras, J.; Mueses, M.; Torres Palma, R.A.; Machuca Martínez, F.; Porras López, Jazmín (Elsevier BV, 2019)
Sensitizers are being used to improve the photocatalytic activity of semiconductors in the visible light region of the solar spectrum. Different types of dyes are reported as sensitizer agents, such as ruthenium complex molecules, porphyrins and Pt complexes, which are critically assessed because they are hazardous substance. Therefore, it is necessary to replace these compounds with safer sensitizer like organic dyes. This work evaluated the photocatalytic degradation of diclofenac using two different types of organic dyes (Perinaphtenone and Eosin-Y) as sensitizer agents. The catalyst concentration [0.15; 0.35 g/l], source of light (UVA – Vis) and type of dye were evaluated. The data obtained can be useful to classify organic dyes that could be employees as sensitizers and which is the wavelength more adequate to use as an energy source. The Kapp for the reaction has values between 1*10−3 to 5*10−3 min−1 for UVA, 3*10−4 to 3*10−3 min−1 for Vis and 2*10−3 to 6*10−3 min−1 for UV–Vis.
Keywords: Organic Dyes; Dye-sensitized; Perinaphtenone; Sensitization; Visible light; Photocatalysis; Fotocatálisis